2020
DOI: 10.1017/dmp.2020.396
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Implementing Strategies to Reduce the Risk of Self-Contamination of Health Care Workers Caused by Doffing of Personal Protective Equipment During the COVID-19 Pandemic

Abstract: During the current COVID-19 pandemic, there is estimation that tens of thousands health care workers got infection. The doffing of personal protective equipment (PPE) has been identified an important place and procedure which might influence self-contamination of health care workers. Newer evidences suggest that in addition to existing infection control standards, there is an urgent need for incorporation of various recent information and advancements pertaining to structural and process to reduce self-contami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…Identifying and implementing strategies and approaches to reduce the chances of infection among healthcare workers is a priority for any healthcare facility, especially during the pandemic. In addition to existing infection control standards, there is an urgent need for incorporating recent information and advancements to reduce contamination of healthcare workers, including dentists [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Identifying and implementing strategies and approaches to reduce the chances of infection among healthcare workers is a priority for any healthcare facility, especially during the pandemic. In addition to existing infection control standards, there is an urgent need for incorporating recent information and advancements to reduce contamination of healthcare workers, including dentists [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the donning phase is associated with a low risk of contamination, doffing is a critical phase and greatly increases the risk of contamination of caregivers [5][6][7][8][9]. One of the strategies that effectively contributes to reducing staff self-contamination is doffing in structured areas dedicated to the removal of PPE [10,11]. However, this strategy is difficult to apply in the prehospital field, where health care workers must often doff PPE on site.…”
Section: Background and Importancementioning
confidence: 99%
“… 3 It has been reported that 40 percent of HCP make errors while doffing their PPE, causing them to self-contaminate skin and clothing. 4 , 5 , 6 , 7 , 8 Therefore, it is recommended that PPE monitors be used to promote their colleagues’ safety by guiding them through the donning and doffing processes. 6 , 9 , 10 Early in 2020, the University of North Carolina Medical Center (UNC-MC) chose to incorporate PPE monitors as part of its comprehensive prevention strategy to reduce the risk of staff self-contamination with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 5 , 6 , 7 , 8 Therefore, it is recommended that PPE monitors be used to promote their colleagues’ safety by guiding them through the donning and doffing processes. 6 , 9 , 10 Early in 2020, the University of North Carolina Medical Center (UNC-MC) chose to incorporate PPE monitors as part of its comprehensive prevention strategy to reduce the risk of staff self-contamination with COVID-19. This paper describes the implementation and use of PPE monitors to observe staff donning and doffing PPE in areas treating known or suspected COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%